Perlakuan Akun Aktiva Tetap Berwujud Menurut Sak Dan Perpajakan Terhadap Laporan Keuangan (Study Kasus Pada PT Iwatani Industrial Gas Indonesia) - Eko Nurochman (GLOBAL SCIENTS PUBLISHER, 2024)
This study aims to analyze the differences in the treatment of tangible fixed asset accounts based on Financial Accounting Standards (SAK) and tax regulations and their impact on the company's financial statements. The case study was conducted at PT Iwatani Industrial Gas Indonesia with a qualitative approach. Data were collected through interviews, document analysis, and literature studies. The results of the study indicate significant differences in the recognition and measurement of tangible fixed assets between SAK and tax regulations. These differences have an impact on elements of the financial statements, such as the book value of assets, depreciation expense, and the company's fiscal profit. These impacts indicate the need for companies to understand the differences between the two standards to support compliance and optimization of financial statements. This study provides a practical contribution by suggesting a more integrated reporting strategy and encouraging harmonization between accounting standards and tax regulations.